Assessing Soft Skills Development Among Orphans and Vulnerable Children in Nigerian Primary Schools: A Focus on Social Studies - Salami, Ishola A.; Oyefeso, Esther O.; Akinjobi, Adenike; Owolabi, Folashade (PrimaryEdu : Journal of Primary Education, 2024)
The majority of Orphans and Vulnerable Children (OVC) in Nigeria are grossly at a disadvantage for several reasons, so there is a need to ensure the development of soft skills during their school year to make them self-reliant and employable after completion of schooling. The study aimed to assess the pupils' soft skills, such as courtesy, flexibility, team spirit, responsibility and integrity. A descriptive survey research design and a multi-stage sampling procedure was adopted. Random sampling techniques were used in selecting three states in South Western Nigeria, namely, Ogun, Osun and Oyo States, while purposive sampling technique was used to select two major schools for orphans and people with special needs, each from the selected states. Total enumeration was adopted to include all the primary II pupils, totalling 95 participants. Primary Pupils Soft Skills Observation Schedule (r=0.85), was used to collect data. Data were analysed using descriptive and inferential statistics at 0.05 significance level. The pupils had the highest development mean score in courtesy (mean = 1.85), followed by flexibility (mean = 1.80); then team spirit (mean = 1.74), responsibility (mean = 1.73), while integrity (1.67) was the least developed. Recommendations were made based on findings.